Prognostic significance of liver stiffness assessed by fibrosis‐4 index in patients with heart failure - Masafumi Takae; Koichiro Fujisue; Eiichiro Yamamoto; Koichi Egashira; Takashi Komorita; Fumi Oike; Taiki Nishihara; Masahiro Yamamoto; Kyoko Hirakawa; Noriaki Tabata; Takanori Tokitsu; Kenshi Yamanaga; et al. (ESC Heart Failure, 2021)
Abstract Background Heart failure (HF)‐related congestive hepatopathy is a well‐recognized problem in management of HF. The fibrosis‐4 (FIB4) index calculated by [age × aspartate aminotransferase (IU/L)/platelet count (109/L) × square root of alanine aminotransferase (IU/L)] is useful for evaluating liver stiffness. We aimed to investigate the impact of the FIB4 index on prognosis in patients with HF. Methods and results Consecutive HF patients referred for hospitalization at Kumamoto University Hospital, Japan, were registered between 2006 and 2015. We observed cardiovascular outcomes in each type of HF [HF with reduced left ventricular ejection fraction (LVEF) (HFrEF), HF with mid‐range LVEF (HFmrEF) and with preserved LVEF (HFpEF)] according to their FIB4 index; Group 1 (FIB4 index <1.3), Group 2 (FIB4 index: 1.3–2.67), and Group 3 (FIB4 index >2.67). This study enrolled 83 HFrEF patients, 117 HFmrEF patients, and 504 HFpEF patients. In HFpEF patients, the Kaplan–Meier curve revealed that Group 3 had a significantly higher rate of total cardiovascular events compared with the other two groups. By contrast, the occurrences of total cardiovascular events were not different among three groups in HFrEF and HFmrEF patients. Multivariate Cox proportional hazard analysis with significant factors in univariate analysis identified that the FIB4 index as an independent and significant predictor for future total cardiovascular events in HFpEF patients (hazard ratio: 1.09, 95% confidence interval: 1.03–1.15, P = 0.001). Conclusions The FIB4 index was a significant predictor for total cardiovascular events in HFpEF.